Supramolecular Photothermal Nanomedicine Mediated Distant Tumor Inhibition via PD-1 and TIM-3 Blockage - Huang, Tong-Yi; Huang, Guang-Liang; Zhang, Chun-Yang; Zhuang, Bo-Wen; Liu, Bao-Xian; Su, Li-Ya; Ye, Jie-Yi; Xu, Ming; Kuang, Ming; Xie, Xiao-Yan (Frontiers in Chemistry, 2020)
Supramolecular nanoparticles for photothermal therapy (PTT) have shown promising therapeutic efficacy to the primary tumor and great potential for turning the whole-body immune-microenvironment from ‘cold’ to ‘hot’, which allows the simultaneous treatment for primary tumor and metastatic site. In this work, we develop a liposome-based PTT nanoparticle through self-assembly of FDA approved intravenous injectable lipids and a photothermal agent, indocyanine green (ICG). The obtained ICG-Liposome shows long-term storage stability, high ICG encapsulation efficiency (> 95%), and enhanced near-infrared (NIR) light-triggered photothermal reaction both in vitro and in vivo. The ICG-Liposome efficiently eradicated the primary tumor upon laser irradiation in two colon cancer animal models (CT26 and MC38) and promoted the infiltration of CD8 T cells to distant tumors. However, PTT from ICG-liposome shows only a minimal effect on the inhibition of distant tumor growth in long-term monitoring, predicting other immunosuppressive mechanisms that exist in the distant tumor. By immune-profiling of the tumor microenvironment, we find that the distant tumor growth after PTT highly correlates to compensatory upregulation of immune checkpoint biomarkers, including program death-1 (PD-1) and T-cell immunoglobulin and mucin domain-containing protein 3 (TIM-3), in tumor-infiltrating CD8 T cells. Based on this mechanism, we combine dual PD-1 and TIM-3 blockade with PTT in an MC38 tumor model. This combo successfully clears the primary tumor, generates a systemic immune response, and inhibits the growth of the distant tumor. The ICG-Liposome combined PD-1/TIM-3 blockade strategy sheds light on the future clinical use of supramolecular PTT for cancer immunotherapy.